2016
DOI: 10.1101/cshperspect.a026435
|View full text |Cite
|
Sign up to set email alerts
|

Nonhistone Lysine Methylation in the Regulation of Cancer Pathways

Abstract: Proteins are regulated by an incredible array of posttranslational modifications (PTMs). Methylation of lysine residues on histone proteins is a PTM with well-established roles in regulating chromatin and epigenetic processes. The recent discovery that hundreds and likely thousands of nonhistone proteins are also methylated at lysine has opened a tremendous new area of research. Major cellular pathways involved in cancer, such as growth signaling and the DNA damage response, are regulated by lysine methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 112 publications
1
89
0
Order By: Relevance
“…Biological functions for lysine methylation is best characterized on histone proteins and the regulation of epigenetics and chromatin biology (Chi et al, 2010). Beyond histones, there is a growing appreciation that a number of non-histone proteins (e.g., p53, RB, RelA) are modulated by lysine methylation (Carlson and Gozani, 2016). In the human proteome, there are predicted to be greater than 100 KMTs that belong to one of two protein methylase families: SET (Su(var)3-9, Enhancer-of-zeste, Trithorax) domain enzymes and 7bS (seven-b strand) enzymes (Clarke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Biological functions for lysine methylation is best characterized on histone proteins and the regulation of epigenetics and chromatin biology (Chi et al, 2010). Beyond histones, there is a growing appreciation that a number of non-histone proteins (e.g., p53, RB, RelA) are modulated by lysine methylation (Carlson and Gozani, 2016). In the human proteome, there are predicted to be greater than 100 KMTs that belong to one of two protein methylase families: SET (Su(var)3-9, Enhancer-of-zeste, Trithorax) domain enzymes and 7bS (seven-b strand) enzymes (Clarke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We are also learning the importance of crosstalk between protein and DNA methylation reactions (9) and among protein methylation, phosphorylation, acetylation, and ubiquitination reactions (10)(11)(12). Finally, we are discovering how alterations in protein methylation pathways can lead to human pathology, particularly in cancer (13)(14)(15).…”
Section: Regulation Of Biological Function By Protein Methylation Reamentioning
confidence: 99%
“…Most lysine methylation regulators localize to the nucleus at least some of the time (Figure 1) (Carlson and Gozani, 2016). However, beyond chromatin function, few studies have revealed mechanisms of lysine methylation signaling in the nucleus.…”
Section: Lysine Methylation Inside the Nucleusmentioning
confidence: 99%
“…The identification of new sites of lysine methylation has far outpaced functional annotation. In fact, only a small fraction of non-histone lysine methylation sites have been assigned a function ( Supplementary Table 1) and the majority of these studies have been limited to a few proteins (e.g., p53, ER, RB1), which have been extensively reviewed elsewhere (Biggar and Li, 2015;Biggar et al, 2017;Carlson and Gozani, 2016). Here, we discuss key findings in recent years that have expanded our understanding and appreciation of the functional role of lysine methylation in molecular processes by finetuning non-histone protein function (Figure 2).…”
Section: Introductionmentioning
confidence: 99%